Pemupukan Patriotisme Melalui Pendidikan Multikultural Dalam Pendidikan Sejarah di Malaysia: Satu Tinjuan Perspektif - Seman, Ahmad Ali Bin (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2009)
The purpose of this research is to show up the variant of ethnicgroup in Malaysia, it is an impression to Malaysia as a country with politicalinsight, state to construct the power of country as a sovereign govern-ment. In contrary, history education has a part to increase the sociali-zation as poUrical consciousness in young generation, defend the spirit ofnationalism which is important element to develop a good characteristicand quality of citizen.Keywords:Patriotisme, multicultur, perpad